Authorities' Roles and Organizational Issues in Systemic Bank Restructuring - Nyberg, Peter (IMF Working Papers; Working Paper ;, 1997)
Systemic bank restructuring must be the responsibility of one government authority only, with other authorities providing support and analytical help. The restructuring authority, whose tasks are enumerated and discussed, should preferably be a separate and temporary agency reporting to the finance ministry. Other solutions are possible but not recommended. Parliament should be involved in setting priorities and supervising the process, but political interference in restructuring operations should be avoided. Practical issues to consider include ensuring efficient cooperation between authorities; the arrangement of problem asset workout and recovery; and restructuring of politically sensitive enterprises.